Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd000125.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Local opinion leaders: effects on professional practice and health care outcomes

Abstract: Background-Clinical practice is not always evidence-based and, therefore, may not optimise patient outcomes. Opinion leaders disseminating and implementing 'best evidence' is one method that holds promise as a strategy to bridge evidence-practice gaps. Objectives-To assess the effectiveness of the use of local opinion leaders in improving professional practice and patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
177
0
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(186 citation statements)
references
References 67 publications
7
177
0
2
Order By: Relevance
“…Ressursbruk som skal støtte en implementeringsprosess blir ofte glemt eller nedprioritert, slik det også ble i dette prosjektet. De foreslåtte tiltakene som skulle imøtekomme forventede utfordringer, slik som akademisering (41) og aktivisering av «superbrukere» (42), uteble fordi driften ikke tillot det. Grol og Wensing (43) hevder at mennesker beveger seg i ulikt tempo fra en endringsfase til neste, og at tiltakene må tilpasses i forhold til dette.…”
Section: Resultatets Betydningunclassified
“…Ressursbruk som skal støtte en implementeringsprosess blir ofte glemt eller nedprioritert, slik det også ble i dette prosjektet. De foreslåtte tiltakene som skulle imøtekomme forventede utfordringer, slik som akademisering (41) og aktivisering av «superbrukere» (42), uteble fordi driften ikke tillot det. Grol og Wensing (43) hevder at mennesker beveger seg i ulikt tempo fra en endringsfase til neste, og at tiltakene må tilpasses i forhold til dette.…”
Section: Resultatets Betydningunclassified
“…[13][14][15]44 Furthermore, there is no consensus on which interventions are the most effective. A recent Cochrane review on educational meetings concluded that while didactic education can change practice (median adjusted risk difference ¼ 7%), meetings that are partially or largely interactive are more effective (median adjusted risk difference ¼ 14%).…”
Section: From Knowledge To Actionmentioning
confidence: 99%
“…48 A review of educational outreach visits, also referred to as ''university-based educational detailing,'' ''academic detailing,'' or ''educational visiting,'' concluded that these visits, either alone or combined with other interventions, produced changes in clinical practice (median adjusted risk difference in compliance desired practice was 6%). 14 Flodgren et al 15 concluded that interventions using opinion leaders reduced non-compliance with desired practice in health professionals (10% absolute decrease), although little is IMT ¼ inspiratory muscle training; COPD ¼ chronic obstructive pulmonary disease known about the factors associated with the success of this intervention. A recent review reported that interventions tailored to address prospectively identified barriers to change are more likely to improve professional practice than either no intervention or dissemination of guidelines or educational materials alone.…”
Section: From Knowledge To Actionmentioning
confidence: 99%
See 2 more Smart Citations